Embedded allocutivity in Basque. (30th July 2022) - Haddican, Bill; Etxeberria, Urtzi
Abstract: Recent work has described allocutive marking in finite embedded contexts in Tamil and Magahi, where allocutivity interacts with indexical shift. It has been proposed that allocutive marking reflects agreement with a silent addressee‐related DP present in all finite clauses even when no indexical shift applies. A prediction of this approach is the possibility of varieties with embedded allocutive marking but no indexical shift. This article argues that some southern Basque dialects instantiate this possibility. In addition, novel evidence is presented suggesting that the syntax of allocutivity is related to the syntax of direct‐address expressions in these dialects.